That night on thistle lane ebook - Neggers, Carla (Swift River Valley, 2013)
New York Times bestselling author Carla Neggers returns with the second book in the Swift River Valley series, That Night on Thistle Lane, following Secrets of the Lost Summer. More than just make-believe Librarian Phoebe O'Dunn deals in stories, but her passion for history has taught her that happy endings are rare. Her life in Knights Bridge, Massachusetts, is safe and uneventful...until she discovers the hidden room. Among its secrets is a cache of vintage clothing, including a spectacular gown-perfect for a gala masquerade in Boston. In the guise of a princess, Phoebe is captivated by a handsome swashbuckler who's also adopted a more daring persona. Noah Kendrick's wealth has made him wary, especially of women: everybody wants something. When Noah and Phoebe meet again in Knights Bridge, at first neither recognizes the other. And neither one is sure they can trust the magic of the night they shared--until an unexpected threat prompts them to unmask their truest selves. After all, it takes more than just the right costume to live out your personal fairy tale. It takes heart...and the courage to be more than you ever dreamed.